DETERMINATION OF SOME BETA-BLOCKERS AS DABSYL DERIVATIVES BY HPLC - ALPERTUNGA, B; SUNGUR, S; ERSOY, L; MANAV, SY (WILEY-V C H VERLAG GMBH, 1990)
A HPLC method has been developed that permits the sensitive determination of beta adrenergic blocking drugs, including acebutolol, metoprolol, oxyprenolol, pindolol, and propranolol. These compounds were converted to their chromophoric dabsyl derivatives and were separated by a reversed phase chromatographic column (.mu.-Bondapak C18) with methanol-water (75:25) as isocratic mobile phase. The derivatives were detected by a variable wavelength dedector operating at 430 nm. The method was applied to commercial pharmaceutical preparations and the results were statistically compared with those obtained by official methods using t- and F-tests.
Keywords: Pharmacology & Pharmacy; Chemistry